Profiles of civic engagement across educational transitions: Stability and change. - Johnson, Sara K. ; Agans, J. P.; Weiner, M. B; Lerner, Richard M. (Tufts University. Tisch Library., 2016)
Young people’s civic engagement over the transition to adulthood is often sporadic, interspersed with life transitions, and patterned differently acrosspeople. Understanding covariates of patterns of civic engagement, and changes in these patterns, could enhance efforts to promote young adults’civic engagement. Using two time points of data from the Young Entrepreneurs Study (N= 2,364; 61.9% female; 60.9% European American),we identified four profiles of civic engagement: Low Initiative, Moderately Involved, Highly Involved, and Organizers. Profile membership wasmoderately stable, and stability rates were similar regardless of changes in participants’ education status. Participants’ initial levels of contributionideology were related to stability in profile membership; participants with higher initial levels of contribution ideology were more likely to beclassified in the Highly Involved profile at both waves. Implications for future research and applications are discussed.